A View to the Future: Opportunities and Challenges for Food and Nutrition Sustainability. Issue 4 (18th March 2020) - Kennedy, Eileen; Raiten, Daniel; Finley, John
ABSTRACT: The challenges to achieving sustainability in food and nutrition are daunting. The present paper summarizes 3 individual papers that are part of this special collection. The lynchpin for synthesizing the papers is sustainability and food systems. Within each of these domains are embedded a myriad of factors, each of which are essential for the sustainable transformation of food systems. Controversies surrounding the concepts of a healthy diet, sustainable agricultural production, and maximizing the dietary impacts of food environments are discussed and evaluated in the context of the current food and nutrition landscape. Abstract : Food systems globally are changing rapidly. As food systems evolve, there have been burgeoning rates of overweight and obesity. There is now a clarion call for transformational changes in food systems, worldwide, that enhance diet quality and improve nutritional status. The challenges is daunting. Food Systems are expected to improve both under and over nutrition, and to do so in a manner that is respectful of natural resources. This paper assesses challenges for developing sustainable food systems and implications for designing effective strategies.